Nutrient versus seed bank depletion approaches to controlling exotic annuals in threatened Box Gum woodlands. (26th July 2015) - Cole, Ian Arthur; Prober, Suzanne; Lunt, Ian; Koen, Terry B.
Abstract: Control of exotic annuals is often a priority when restoring degraded grasslands or shrublands. This study evaluated combinations of nutrient‐depleting (carbon addition) and seed bank‐depleting approaches for controlling exotic annuals, and compared the seed bank depletion technique of spring burning with the more easily applied technique of pulse grazing. Treatments were applied in two Box Gum woodlands over 4 years. Consistent with earlier studies, carbon addition dramatically reduced exotic annuals and available nutrients in all 3 years at both sites. Exotic annual grass abundance was significantly reduced in burnt plots following the first year and in grazed plots following the second year of application. Spring burning or grazing did not reduce available nutrients or exotic annual broadleaf abundance at either site. The effect of carbon addition on exotic annuals and available nutrients was so powerful that no additional benefit of the combination treatments was found, although at one site burning and grazing slightly reduced the effectiveness of carbon addition in suppressing broadleaf exotic annuals. We conclude that nutrient‐depleting approaches are most effective because they control both exotic annual grasses and broadleaf exotics annuals, but given their expense seed bank‐depleting approaches may be more practical where exotic annual grasses dominate. In particular, pulse grazing is readily applied across large areas, offering a relatively simple tool that if appropriately implemented could enhance outcomes of restoration investments in vegetation communities invaded by exotic annual grasses.